Somalia : Second Review Under the Staff-Monitored Program and Request for Three-Year Arrangements Under the Extended Credit and The Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Somalia. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Somalia's Second Review Under the Staff-Monitored Program and Request for Three-Year Arrangements Under the Extended Credit and the Extended Fund Facility. The three-year financing package will support the implementation of the authorities' National Development Plan and anchor reforms between the heavily indebted poor countries Decision and Completion Points. Reforms will focus on a continued strengthening of public finances to meet Somalia's development needs in a sustainable manner; a deepening of central bank capacity; improvement of the business environment and governance; and enhancing statistics. Risks to the program and outlook remain elevated, although there is also upside potential. The immediate political risks concern the upcoming elections, while frequent climate shocks continue to contribute to agricultural loss and human displacement. On the upside, greater-than-expected impact from reforms under the program and additional development financing, together with the development of new industries, could lead to higher and more inclusive growth than the baseline.